WRITE UPDATED NEWS REPORTS TO IMPROVE THE WRITING ABILITY OF THE TENTH GRADE STUDENTS OF MIA 1 IN HIGH SCHOOL WAHIDIYAH KEDIRI ACADEMIC YEAR 2018/2019 - Nafi’yah, Siti; Nurrahma, Avinta Ika (JURNAL KOULUTUS, 2018)
There are many students who experience difficulties in the field of writing English because they lack English vocabulary, are weak in grammar, have difficulty in choosing words too. This makes it difficult for them to write and they think that writing English is difficult. Most students in the tenth grade of MIA 1 High School Wahidiyah Kediri get a low score in the field of writing as evidenced by the acquisition of scores under the minimun graduation criteria of 76. This study was conducted to improve the writing skills of the tenth grade ofMIA 1 High School Wahidiyah Kediri in the year 2018/2019 by writing updated news reports. The purpose of this study is to describe whether there is a significant development in the ability to write news in the tenth grade of MIA 1 High School Wahidiyah Kediri. This research is an pre-experimental research with pre-test and post-test. This study focuses on the application of up-to-date news writing to the tenth grade of MIA 1 High School Wahidiyah Kediri in the 2018/2019 school year. After treatment, the students were given a post-test to measure their level of understanding in the material that had been given and developed in the form of writing. The results of the post-test showed that these students had developed in a good category with an average value of 57,77 to 81,07 Key words: writing, improve writing ability, news writing.